A Novel, Integron-Regulated, Class C β-Lactamase - Maria-Elisabeth Böhm; Mohammad Razavi; Carl-Fredrik Flach; D. G. Joakim Larsson (MDPI AG, 2020)
AmpC-type β-lactamases severely impair treatment of many bacterial infections, due to their broad spectrum (they hydrolyze virtually all β-lactams, except fourth-generation cephalosporins and carbapenems) and the increasing incidence of plasmid-mediated versions. The original chromosomal AmpCs are often tightly regulated, and their expression is induced in response to exposure to β-lactams. Regulation of mobile ampC expression is in many cases less controlled, giving rise to constitutively resistant strains with increased potential for development or acquisition of additional resistances. We present here the identification of two integron-encoded ampC genes, blaIDC-1 and blaIDC-2 (integron-derived cephalosporinase), with less than 85% amino acid sequence identity to any previously annotated AmpC. While their resistance pattern identifies them as class C β-lactamases, their low isoelectric point (pI) values make differentiation from other β-lactamases by isoelectric focusing impossible. To the best of our knowledge, this is the first evidence of an ampC gene cassette within a class 1 integron, providing a mobile context with profound potential for transfer and spread into clinics. It also allows bacteria to adapt expression levels, and thus reduce fitness costs, e.g., by cassette-reshuffling. Analyses of public metagenomes, including sewage metagenomes, show that the discovered ampCs are primarily found in Asian countries.